2014
DOI: 10.1155/2014/731720
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Students’ Satisfaction with Web Based Learning System in Blended Learning Environment

Abstract: Blended learning became the most popular educational model that universities apply for teaching and learning. This model combines online and face-to-face learning environments, in order to enhance learning with implementation of new web technologies and tools in learning process. In this paper principles of DeLone and Mclean success model for information system are applied to Kano two-dimensional model, for categorizing quality attributes related to satisfaction of students with web based learning system used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 22 publications
1
20
0
2
Order By: Relevance
“…Students' satisfaction, acceptance, expectations, and attitudes play a significant role in evaluating the efficiency of the instructional process in a blended learning environment (Akkoyunlu & Soylu, 2008). However, there are insufficient studies investigating students' satisfaction with a blended learning system used to support teaching and learning in a blended environment (Bauk et al, 2014). Therefore, this study seeks to examine the students' satisfaction of blended learning course.…”
Section: Introductionmentioning
confidence: 99%
“…Students' satisfaction, acceptance, expectations, and attitudes play a significant role in evaluating the efficiency of the instructional process in a blended learning environment (Akkoyunlu & Soylu, 2008). However, there are insufficient studies investigating students' satisfaction with a blended learning system used to support teaching and learning in a blended environment (Bauk et al, 2014). Therefore, this study seeks to examine the students' satisfaction of blended learning course.…”
Section: Introductionmentioning
confidence: 99%
“…According to the findings of the study, system quality was the only variable that affected the benefits and usefulness of the virtual education system through both the direct and indirect paths. According to the DeLone and McLean model, system quality refers to aspects of the information system itself, such as data reception speed, easy access, system authenticity, responsiveness, flexibility and user-friendliness 8 11 . These findings are consistent with the results obtained by Pérez-Mira (2010) and Boroufar et al .…”
Section: Discussionmentioning
confidence: 99%
“…(2011) also found that the learners’ level of satisfaction has the greatest direct effect on net benefits (7 The term ‘net benefits’ refers to the main benefits achieved by user’s increased use and satisfaction 8 11 . The satisfaction of the users of a system plays a large role in the success and continued use of a system 8 . In the present study, student satisfaction was affected by system quality and service quality.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the paper is to present the possibilities of the application of Kano method for the evaluation of the teaching staff quality. To this end, the analysis of literature and Kano questionnaire were employed, with the usefulness of Kano questionnaire in this type of research being verified in numerous publications (Grudowski, Dembowski 2012: 77-87;Malinowska 2010: 467-477;Arefi et al 2012:347-353;Sia, Muthusamy 2012: 230-235;Malinowska et al 2014: 235-247;Bauk et al 2014;Dominici, Palumbo 2013: 87-96;Mayers, Jones 2012: 5-18;Taifa, Desai 2016: 569-582)…”
Section: Introductionmentioning
confidence: 99%